Implementasi Algoritma Kriptografi RSA untuk Keamanan Transmisi Data pada Sistem Monitoring Energi Listrik Berbasis IoT - Rajawali Rajawali; Syamsul Bahri; Kasliono Kasliono (Journal of Information System Research (JOSH), 2026)
Data security is a crucial issue in Internet of Things (IoT) systems used to monitor electricity consumption. This study aims to enhance the security of data transmission in an IoT-based electricity monitoring system by implementing the Rivest–Shamir–Adleman (RSA) cryptographic algorithm. Data from the PZEM-004T sensor is encrypted using the RSA public key and verified with a digital signature before being transmitted to the server. The system was tested under two conditions: without encryption and with RSA encryption, including a simulated ARP spoofing attack using Ettercap. The results show that the system successfully rejected manipulated data, with a packet loss rate of 2.08%, which is categorized as “very good” based on the TIPHON standard, and achieved a throughput of approximately 9.88 bit/s. The implementation of RSA proved effective in maintaining data integrity and authenticity, thereby improving the reliability of the IoT-based electricity monitoring system.